The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2320/matertrans.maw201104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photocatalytic Property of TiO<SUB>2</SUB> Columnar Nanostructure Films

Abstract: The rutile TiO 2 films with columnar nanostructure were prepared by combining the glancing angle deposition (GLAD) technique in magnetron sputtering system with the subsequent two-step annealing treatment. Experimental results showed that all the TiO 2 films kept discrete columnar structures as the Ti films deposited by GLAD and accomplished the phase transition from Ti to rutile TiO 2 . Such TiO 2 films performed photocatalytic activity effectively and reusably towards methyl orange under UV light irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…05-0669, 21-1272, and 21-1276 of the ZnAl 2 O 4 , anatase-TiO 2 , and rutile-TiO 2 , respectively. This result was also found similar to the reported works [20,25]. During the preparation of nanoceramic composite material, the concentration of TiO 2 plays a significant role to alter the diameter of the crystallite.…”
supporting
confidence: 92%
“…05-0669, 21-1272, and 21-1276 of the ZnAl 2 O 4 , anatase-TiO 2 , and rutile-TiO 2 , respectively. This result was also found similar to the reported works [20,25]. During the preparation of nanoceramic composite material, the concentration of TiO 2 plays a significant role to alter the diameter of the crystallite.…”
supporting
confidence: 92%
“…However, the RMS of the GLAD sample was 5 nm, i.e., was significantly higher than that of the untilted sample. Moreover, these results are in good correlation with GLAD-related research, as RMS values are usually found to increase with the increasing oblique angle of deposition [24]. Such changes in morphology may lead to a significant decrease in the values of the contact angle of the coatings.…”
Section: Coatings 2018 8 X For Peer Review 4 Of 17supporting
confidence: 81%
“…In the field of optics and microelectronics, physical vapor deposition (PVD) of thin films, allowing the deposition of porous and/or columnar-like structured coatings, has been available for some years. For this purpose, the use of an oblique angle geometrical configuration-or as it is also known, glancing angle deposition (GLAD) method-is frequently exploited [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…SEM images of the TiO 2 films annealed for 1, 2, 3, and 4 hours, respectively, are presented in Figure 4 (cross-sections and surface morphologies). There are almost no differences in discrete columnar morphologies between them [18,21]. They all keep discrete columnar structures as the Ti films deposited by GLAD.…”
Section: Resultsmentioning
confidence: 92%